Use of Technology-Supported Educational Tools in General Music Education and Its Contribution to the Process of Music Education - Gül Gülnihal (Sciendo, 2023)
Introduction: In our current century, technology continues to exist in almost all domains of human life. In this day and age, technological changes and developments make a great contribution to the rapid production of information and easy access to it. As a result of rapidly developing and changing needs, it is considered essential to organize education in line with these needs and to incorporate technology within the education system. In the present study, it was aimed to identify the use of technology supported educational tools in general music education and their contribution to the process of music education.